Inversión extranjera directa en México: comparación entre la inversión procedente de los Estados Unidos y del resto del mundo - Garriga, Ana Carolina (El Colegio de México A.C., 2017)
Are there differences between the foreign direct investment (fdi) that Mexico receives from the United States and the rest of the world? This paper describes the fdi received by the country between 1999 and 2013, detailed according to origin. The flow of fdi to Mexico as a whole and to its component states is analyzed, anddifferences in temporal and spatial patterns of fdi are identified together with their determining factors. This analysis allows us to better understand the fdi received by Mexico, identify regional vulnerabilities and inform decision-making geared towards promoting and retaining investment.